2007
DOI: 10.1212/01.wnl.0000252355.79284.22
|View full text |Cite|
|
Sign up to set email alerts
|

Randomized, blind, controlled trial of transdermal rotigotine in early Parkinson disease

Abstract: Transdermal rotigotine, when titrated to a dosage of 6 mg/24 h, was effective for the treatment of early-stage Parkinson disease in this trial. Adverse events were similar to those found with other transdermal systems and dopamine agonists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
135
1
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(144 citation statements)
references
References 17 publications
4
135
1
4
Order By: Relevance
“…Rotigotine was chosen as the candidate molecule for development since it is one of the most potent D2/D3 non-ergot agonists currently used clinically with proven safety and efficacy records in PD patients. 17,19,28 Rotigotine has essentially no oral bioavailability and is currently administered through the use of a daily transdermal patch. However, the patch often results in skin reactions and may fall off prematurely, leading to issues with patient compliance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rotigotine was chosen as the candidate molecule for development since it is one of the most potent D2/D3 non-ergot agonists currently used clinically with proven safety and efficacy records in PD patients. 17,19,28 Rotigotine has essentially no oral bioavailability and is currently administered through the use of a daily transdermal patch. However, the patch often results in skin reactions and may fall off prematurely, leading to issues with patient compliance.…”
Section: Discussionmentioning
confidence: 99%
“…16 A transdermal system has been developed to provide continuous delivery of the dopamine agonist rotigotine and its use leads to significant improvements in on time and decreased dyskinesia intensities, although this approach has its own limitations, which include local skin reactions and difficulties with adhesion leading to early sloughing off. [17][18][19] Conjugation of pharmaceuticals to stable biodegradable polymers, such as polyethylene glycol and hyaluronic acid, can improve bioavailability of proteins and small molecule drugs. 20 Polyoxazolines (POZs) are one of the bioconjugate polymers that show early promise in drug delivery.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the following other anti-Parkinson medications were allowed after 1 month of open-label rotigotine maintenance: monoamine oxidase B inhibitors, anticholinergic agents, N-Methyl-D-aspartate receptor-antagonists (e.g., amantadine), entacapone and modafinil. Complete inclusion and exclusion criteria are published [15][16][17][18][19].…”
Section: Designmentioning
confidence: 99%
“…The benefit of treating patients with early PD with rotigotine has been demonstrated in both short-and long-term studies. Two randomized, placebo-controlled studies of 6-month maintenance (SP512 and SP513) have shown rotigotine transdermal patch to be an efficacious therapy in early-stage PD, producing significant improvements in activities of daily living and motor symptoms, as assessed by UPDRS II + III total score [15][16][17]. The SP702 and SP716 studies were longterm, single-arm, open-label extensions of the SP512 and SP513 studies.…”
Section: Introductionmentioning
confidence: 99%
“…For rotigotine, Watts et al 60 found, with a mean dose of 5.7 mg/24 hours, a decrease in UPDRS subtotal score (part II ADL plus part III Motor) of 5.28 points, compared with placebo. The part III Motor score decreased by 3.5 points.…”
Section: Da Agonists: Phase III Clinical Trial Results Early Pdmentioning
confidence: 99%